Efficacy of Nucleic Acid Amplification Test (NAT) over Enzyme Linked Immuno Sorbent Assay (ELISA) in Detecting Transfusion Transmissible Infections (TTI) among Blood Donors at a Tertiary Care Centre: A Comparative Study - Aramani, Shakuntala Sunil; Bommanahalli, Basavaraj Prabhappa; Kammar, Sourabh Mouneshwar (Annals of Pathology and Laboratory Medicine, 2019)
Background: Background: Blood safety in India becomes prime importance with a large number of blood donors. The donated blood is screened for transfusion transmissible infections (TTI) using immunoassays and nucleic acid amplification Test (NAT). However the risk of infection during window period (WP) might be missed by the immunoassay, which are responsible for most of the TTI. Zero window period might provide complete blood safety. Aim: 1) To study sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy (efficacy) of NAT over enzyme linked immuno sorbent assay (ELISA) methods in detecting TTI among blood donors 2)To assess the impact of introduction of individual donor – nucleic acid amplification test (ID-NAT) by all the blood banks and this study was conducted at blood bank, Gadag institute of medical sciences (GIMS), Gadag, Karnataka, India. Methods: Over a period of 1year & 6 months, a total number of 6000 blood donors, samples were subjected to ELISA and NAT.4th generation ELISA and NAT testing using, transcription mediated amplification(TMA) was used. The results were tabulated in an excel format and data was analyzed using Statistical Package for Social Sciences (SPSS) Software 21st version. Sensitivity, specificity, positive predictive value (PPV), negative predictive value(NPV) and diagnostic accuracy(efficacy) were calculated using Galen and Gambino method. Result: A total of 6000 donors, blood samples were subjected to ELISA and NAT, among them 60 were seroreactive. 52 were NAT reactive and seronegative. The NAT yield was 1 in 113. The present study showed 53.57%, 100%,100%, 99.12% and 99.13% of sensitivity, specificity, PPV, NPV and diagnostic accuracy respectively. Conclusion: NAT could detect human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) cases in blood donor samples those that were undetected by immunoassays. Thus, NAT provides an additional layer of blood safety and provides safest blood pack for donation.